2015
DOI: 10.1016/j.tcb.2014.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of inflammasome activation: recent advances and novel insights

Abstract: Inflammasomes are cytosolic multiprotein platforms assembled in response to invading pathogens and other danger signals. Typically inflammasome complexes contain a sensor protein, an adaptor protein and a zymogen, procaspase-1. Formation of inflammasome assembly results in processing of inactive procasase-1 into an active cysteine protease enzyme, caspase-1, which subsequently activates proinflammatory cytokines, IL-1β and IL-18, and induces pyroptosis, a highly pyrogenic inflammatory form of cell death. Studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
387
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 429 publications
(400 citation statements)
references
References 87 publications
3
387
0
10
Order By: Relevance
“…3 The resulting autocatalysis and activation of caspase-1 lead to maturation and secretion of proinflammatory cytokines IL-1b and IL-18 and, under certain conditions, to induction of pyroptosis, a form of programmed inflammatory cell death. [19][20][21] Recent structural studies have revealed that two successive steps in nucleationinduced and 'prion-like' polymerization -i.e., NLRP3 nucleation of the PYD filaments of ASC and the clustering of pro-caspase-1 within star-like fibers of ASC -are essentially required for the proximity-induced activation of inflammasomes. 22,23 NLRP3 also interacts with NOD2, which plays a nonredundant role in the processing of pro-IL-1b, in a CARDindependent manner.…”
Section: Overview Of the Nlrp3 Inflammasome Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The resulting autocatalysis and activation of caspase-1 lead to maturation and secretion of proinflammatory cytokines IL-1b and IL-18 and, under certain conditions, to induction of pyroptosis, a form of programmed inflammatory cell death. [19][20][21] Recent structural studies have revealed that two successive steps in nucleationinduced and 'prion-like' polymerization -i.e., NLRP3 nucleation of the PYD filaments of ASC and the clustering of pro-caspase-1 within star-like fibers of ASC -are essentially required for the proximity-induced activation of inflammasomes. 22,23 NLRP3 also interacts with NOD2, which plays a nonredundant role in the processing of pro-IL-1b, in a CARDindependent manner.…”
Section: Overview Of the Nlrp3 Inflammasome Complexmentioning
confidence: 99%
“…31 LIGANDS/STIMULI THAT ACTIVATE THE NLRP3 INFLAMMASOME COMPLEX To date, it has been accepted that activation of the NLRP3 inflammasome depends on two signals: a priming signal, required for the upregulation of NLRP3 and pro-IL-1b, and a second signal that triggers assembly into the NLRP3 inflammasome complex. 21,32,33 NLRP3 responds to many stimuli for activation of the inflammasome. 34 The NLRP3 inflammasome is activated by a variety of PAMPs and DAMPs, originating from numerous pathogens, a large number of pore-forming toxins, adenosine triphosphate (ATP), and particulate crystals and aggregates.…”
Section: Overview Of the Nlrp3 Inflammasome Complexmentioning
confidence: 99%
“…Some inflammasomes have been shown to activate caspase-1, convert premature forms of IL1β, IL18, and IL33 to mature forms, and secrete these cytokines into the extracellular space 24 . Each NLR contains N-terminal effector domains, such as the caspase activation and recruitment domain (CARD), pyrin domain (PYD), and the baculoviral inhibitor of apoptosis protein repeat domain (BIR), and are divided into subfamilies based on the composition of these domains [25][26][27] . All NLRs contain a central nucleotide binding and oligomerization (NACHT) domain and most members have a variable number of ligand-sensing C-terminal leucine-rich repeat (LRR) domains [25][26][27] .…”
Section: [H2] Nod-like Receptorsmentioning
confidence: 99%
“…However, our data do not clearly distinguish between dimerization and higher-order oligomerization. It is therefore possible that higher-order complexes form after the initial dimerization event, potentially giving rise to high molecular weight complexes reminiscent of animal inflammasomes (Vanaja et al, 2015).…”
Section: The Oligomerization Of Bph14 Is Implicated In Plant Immunitymentioning
confidence: 99%